Clinical management of snakebite envenoming: Future perspectives - Muhammad Hamza (Toxicon: X, 2021)
Snakebite envenoming is a major cause of morbidity and mortality in rural communities throughout the tropics. Generally, the main clinical features of snakebites are local swelling, tissue necrosis, shock, spontaneous systemic hemorrhage, incoagulable blood, paralysis, rhabdomyolysis, and acute kidney injury. These clinical manifestations result from complex biochemical venom constituents comprising of cytotoxins, hemotoxins, neurotoxins, myotoxins, and other substances. Timely diagnosis of envenoming and identification of the responsible snake species is clinically challenging in many parts of the world and necessitates prompt and thorough clinical assessment, which could be supported by the development of reliable, affordable, widely-accessible, point-of-care tests. Conventional antivenoms based on polyclonal antibodies derived from animals remain the mainstay of therapy along with supportive medical and surgical care. However, while antivenoms save countless lives, they are associated with adverse reactions, limited potency, and are relatively inefficacious against presynaptic neurotoxicity and in preventing necrosis. Nevertheless, major scientific and technological advances are facilitating the development of new molecular and immunologic diagnostic tests, as well as a new generation of antivenoms comprising human monoclonal antibodies with broader and more potent neutralization capacity and less immunogenicity. Repurposed pharmaceuticals based on small molecule inhibitors (e.g., marimastat and varespladib) used alone and in combination against enzymatic toxins, such as metalloproteases and phospholipase A2s, have shown promise in animal studies. These orally bioavailable molecules could serve as early interventions in the out-of-hospital setting if confirmed to be safe and efficacious in clinical studies. Antivenom access can be improved by the usage of drones and ensuring constant antivenom supply in remote endemic rural areas. Overall, the improvement of clinical management of snakebite envenoming requires sustained, coordinated, and multifaceted efforts involving basic and applied sciences, new technology, product development, effective clinical training, implementation of existing guidelines and therapeutic approaches, supported by improved supply of existing antivenoms.